The End of the bananas saga - Guth, Eckart (2012)
Outlines the origins of the problem of the bananas trade dispute between the EU, several Latin America countries and the United States and describes the attempts to resolve the issue through the WTO Dispute Settlement Mechanism. Analyses the negotitions which includes with the Geneva Agreement on Trade in Bananas (GATB). Assess the benefits of the GATB for the main parties involved.